The use of real-time fMRI neurofeedback to enhance post-stroke motor recovery - Sanders, Z-B (2021)
Real-time fMRI neurofeedback is a tool that allows individuals to self-modulate their ongoing brain activity. This may have clinical potential in disorders which are associated with aberrant brain activity, for example in stroke-induced hemiparesis.